Pengelolaan Aset Tanah Milik Pemerintah Daerah Provinsi Gorontalo Yang Masih Di Kuasai Dan Di Tempati Oleh Pensiunan Kehutanan: (Studi Kasus :Jl Jaksa Agung Supraptop Kota Gorontalo ) - Ferdy Hasan; Weny Almoravid Dungga; Zamroni Abdusammad (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
The purpose of this research is to find out the management of the assets of the Gorontalo provincial government in the form of land and buildings that are controlled and occupied by the community and to find out the factors that cause these assets to be controlled. The research method used in this research is empirical.The results of the study found that the management of the assets of the Regional Government of the Gorontalo Province in the form of land and buildings owned and occupied by the community has not gone well, because until now the land that is still occupied by retirees from the Ministry of Forestry of North Sulawesi Province has not met a common ground, because the pensioners still stayed despite attempts at negotiation and even being given an order to vacate the location. This is also constrained by the absence of clear regulations to deal with this, because retirees ask for funds to build houses elsewhere. While the factor that causes these assets to be controlled is the absence of clear regulations as a guideline for solving problems, then the location factor is the place was delegated from the North Sulawesi government and the administrative process was not managed properly by the Gorontalo Province, finally the economic factor, because the retiree does not have the budget to build another house elsewhere if he has to leave the place.